First record of a hydrozoan (Cnidaria, Hydrozoa) growing on a sigalionid scaleworm (Annelida, Sigalionidae) - Cruz-Gómez, Christopher; Mendoza-Becerril, María A. (Zootaxa, 2025)
The scaleworm Pelogenia fimbriata (Hartman, 1939) collected from Secas Islands, Panama, during the Allan Hancock Pacific Expedition in 1916, was not only recognized as an undescribed species at the time of discovery but has also revealed a new finding almost nine decades after its description. A paratype of P. fimbriata was examined in the Natural History Museum of Los Angeles County, USA and the hydroid Bimeria vestita Wright, 1959 was found attached to an anterior scale of the worm. The interaction between B. vestita and P. fimbriata in this study represents the first record of epibiosis of a hydroid on a sigalionid scaleworm. This discovery contributes to our understanding of epibiosis in Hydrozoa and opens new avenues for further research in this area.